Electromagnetic radiation absorption enhancement in graphene by diffraction grating - Yakovleva, Marina A.; Batrakov, Konstantin G. (Journal of the Belarusian State University. Physics, 2018)
In the paper the possibility to increase significantly the terahertz radiation absorption in graphene by a metallic grating is studied theoretically. The solution of this problem consists in expansion of the fields in the Floquet modes and application of the boundary conditions for the tangential components of an electromagnetic field. Due to diffraction of an electromagnetic wave from the grating and to interference of the waves, it is possible to achieve the concentration of the electromagnetic field energy in the region of the graphene location. It is shown that almost complete absorption of electromagnetic radiation in an atomically thin layer of graphene is achieved for reflection and transmission gratings with the particular physical parameters, that is several times higher than the absorption in a free-standing graphene layer of the same parameters. The obtained results can be used for design of detectors and sensors in the rapidly developing area of terahertz spectroscopy.